Web service discovery: Rationale, challenges, and solution directions - Ahmet Vedat Tokmak (17773479) (2024)
Service Oriented Architecture (SOA) is a methodology that promotes cooperation between services with diverse, but connected functions. Web Service technology paved the way for microservice architecture as it is a feature of modern web applications that resulted from the rise of SOA. With the proliferation of self-contained services, the ease of finding has emerged as a critical concern. Due to the increasing number of services that perform identical tasks, it has become difficult for users to select the most feasible service. Providing the most relevant service for the customer quickly is a crucial infrastructure task, and undiscovered services increase ecosystem expenses. Syntactic, semantic-conscious, and ontology-based studies have been presented as ways to improve the effectiveness and quality of service discovery techniques. While there are many approaches that have been proposed and validated for service discovery in literature, these studies are fragmented and there is a lack of overview of the techniques of web service discovery. As such, we conduct a Systematic Literature Review (SLR) study to review the existing body of knowledge surrounding service discovery and discuss the state-of-the-art. We present an overview of the techniques and empirical evidence by identifying, analyzing, and classifying the papers. Among the 764 papers we retrieved, 54 papers were included. We provide a comprehensive analysis of methodologies and tools for discovering web services. Other Information Published in: Computer Standards & Interfaces License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.csi.2023.103794